ATTENUATION OF SWIMMING-INDUCED OXIDATIVE STRESS BY COMPOSITE HERBAL SUPPLEMENT ON ANTIOXIDATIVE PARAMETERS IN MALE RAT - DEBANKA SEKHAR MISRA,; DEBIDAS GHOSH,; RAJKUMAR MAITI, (International Journal of Pharma and Bio Sciences, 2013)
The present study has been designed to find out the antioxidant potency of composite methanolic extract on swimming-induced oxidative damage on packed erythrocytes in Wistar strain male albino rat. Extract was administered at the dose of 40 mg/100 g body weight/day/rat orally by gavage for 15 days period to experimentation followed by co-treatment of the aforesaid extract at the same dose for 28 days of swimming. In swimming group significant diminution resulted in the activities of catalase, peroxidase, glutathione-S-transferase, superoxide dismutase; whereas, elevation in the level of thiobarbituric acid reactive substances and conjugated dienes in packed erythrocytes in comparison to control. The levels of all these parameters were completely recovered towards the extract treated group. The extract possesses no general toxic effect observed from serum glutamate oxaloacetate transaminase and glutamate pyruvate transaminase activities. Such results conclude that above extract has a significant protective effect on swimming-induced oxidative damage. The antioxidant potency of composite extract was compared with vitamin C.